Patients with blunt traumatic thoracic aortic injury treated with TEVAR present increased flow dynamics alterations and pulse wave velocity: a 4D flow CMR study. (25th November 2020) - Guala, A; Gil Sala, D; Ruiz-Munoz, A; Garcia Reyes, M.E; Dux-Santoy, L; Teixido-Tura, G; Tello, C; Cinque, A; Valente, F; Lopez Sainz, A; Galian Gay, L; Ferreira, I; et al.
Abstract: Background: Thoracic endovascular aortic repair (TEVAR) is widely used for the treatment of blunt traumatic thoracic aortic injuries. Aortic flow dynamics and mechanical implications of this intervention are poorly investigated and may be of particular interest in the long-term follow-up of these mostly young patients. Purpose: To assess whether the presence of TEVAR in a cohort of otherwise healthy subjects was related to dilation of the proximal aorta or increase in aortic stiffness and flow alterations. Methods: Nineteen patients who underwent TEVAR implantation after a traumatic injury of the thoracic descending aorta (DAo) (10.0±6.1 years from intervention) and 44 healthy volunteers (HV) underwent 4D flow CMR to compute ascending aorta (AAo) pulse wave velocity (PWV), a marker of aortic stiffness, systolic flow reversal ratio (SFRR), quantifying backward flow during systole and in-plane rotational flow (IRF), measuring in-plane strength of helical flow. IRF and SFRR were assessed at 20 planes between the sinotubular junction and the mid thoracic DAo. Aortic diameters were measured using double-oblique cine CMR. Results: Patients with TEVAR and HV did not differ in age, sex, body surface area, blood pressure and DAo diameter distal to TEVAR (Table). However, TEVAR patients presented larger diameters at the sinus of Valsalva and AAo, increased AAo PWV and strong flow alterations: IRF was reduced from the distal AAo to the proximal DAo, while SFRR was increased in the whole thoracic aorta (Figure). Conclusions: In patients with blunt traumatic thoracic aortic injury treated with TEVAR the aorta proximal to TEVAR is dilated, stiffer and present potentially pathogenic flow conditions. Longitudinal studies are needed to assess whether these alterations have prognostic value and may improve clinical prevention and management of these patients. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): This study has been funded by Instituto de Salud Carlos III, Spanish Ministry of Science and Innovation (PI19/01480). Guala A. received funding from the Spanish Ministry of Science, Innovation and Universities (IJC2018-037349-I).